Leveraging Kustomize for Kubernetes Manifests - Laster, Brent (O'Reilly Media, Inc., 2022)
Kubernetes has achieved unparalleled dominance as the platform for running containerized workloads by automating and simplifying key functions. But the process for working with specifications for Kubernetes workloads, known as manifests, is neither automated nor simplified. Managing these requirements is a high-cost activity up front, and an additional cost burden when reuse is needed. In this report, author Brent Laster shows software developers, Kubernetes administrators, and DevOps engineers how the Kustomize container orchestration system helps simplify and alleviate these challenges. You'll gain an overall understanding of Kustomize, including how this system functions, how it compares to tools like Helm, and how it works with your strategy for managing Kubernetes manifests. In this report, you will: Learn the Kubernetes value proposition for defining and executing workloads Get a brief survey of application deployment and reuse options with Kubernetes Explore the basic tenets of Kustomize's approach Understand how Kustomize compares to the Helm package manager Examine the unique value-adds that Kustomize provides for simplifying reuse.